Report on the development of the national method for the assessment of the ecological status of natural lakes in Greece, using the biological quality element “phytoplankton” - Mavromati, E.; Kemitzoglou, D.; Tsiaoussi, V. (Ministry of Environment, Special Secretariat for Waters, 2018)
This report discusses the development of a national method for the assessment of ecological status of natural lakes in Greece, based on the Biological Quality Element (BQE) “phytoplankton”; it is a revised version of the 2016 report, following comments by JRC and Intercalibration Review Panel experts. The main changes include an amendment to modNygaard index (exclusion of Centrales, see 2.1), the exclusion of a lake’s data from the reference dataset in order to avoid ircularity in the assessment, and construction of pressure response curves with phytoplankton and TP data from lake years 2014 and 2015. At the Mediterranean Lake Geographical Intercalibration Group, Member States defined two common water body types for reservoirs (L-M5/7 and L-M8). In spite of common efforts, within the Mediterranean GIG, there was no possibility to intercalibrate natural Mediterranean lakes because of the absence of common types with enough lakes. As a result, no assessment methods for phytoplankton of natural lakes have been intercalibrated within the Med GIG. The operation of the Greek water monitoring network started in 2012, following the publication of a Joint Ministerial Decision in 2011 and comprises 23 natural lakes. The development of the current assessment method, as described in this report, is based on the data from this national water monitoring network. Natural lakes in Greece are grouped into 3 types: 1) warm monomictic, deep natural lakes with mean depth >9 m (type GR-DNL, 7 lakes), 2) polymictic, shallow natural lakes with mean depth 3-9 m (type GR-SNL, 8 lakes), 3) very shallow lakes < 3 m (type GR-VSNL, 8 lakes).